Digital piracy: Theory - Paul Belleflamme; Martin Peitz (Center for Economic Studies and ifo Institute (CESifo), 2010)
This article reviews recent theoretical contributions on digital piracy. It starts by elaborating on the reasons for intellectual property protection, by reporting a few facts about copyright protection, and by examining reasons to become a digital pirate. Next, it provides an exploration of the consequences of digital piracy, using a base model and several extensions (with consumer sampling, network effects, and indirect appropriation). A closer look at market-structure implications of end-user piracy is then taken. After a brief review of commercial piracy, additional legal and private responses to end-user piracy are considered. Finally, a quick look at emerging new business models is taken.
Keywords: L11; L82; L86; 330; information good; piracy; copyright; IP protection; internet; peer-to-peer; software; music; Digitale Güter; Internet; Virtuelle Gemeinschaft; Tausch; Computerkriminalität; Kriminalitätsökonomik; Urheberrecht; Immaterialgüterrechte; Softwareindustrie; Musikwirtschaft; Geschäftsmodell; Theorie